The amino acid sequence of Lrp is highly conserved in four enteric microorganisms. - Friedberg, D (1995)
Lrp (leucine-responsive regulatory protein) is a global regulator of metabolism in Escherichia coli (J. M. Calvo and R. G. Matthews, Microbiol. Rev. 58:466-490, 1994). The lrp genes from three other enteric microorganisms, Enterobacter aerogenes, Klebsiella aerogenes, and Salmonella typhimurium, were cloned and sequenced. An analysis of these sequences and of the previously determined sequence from E. coli indicated that the vast majority of changes were synonymous rather than nonsynonymous changes. Nucleotide changes occurred at 89 of 492 positions but resulted in amino acid changes at only 2 of 164 positions. This analysis suggests that the Lrp amino acid sequence is highly adapted for function and that almost all amino acid changes lead to a protein that functions less well than the wild-type protein.